ISOLASI DAN IDENTIFIKASI KHAMIR PENGHASIL ASAM INDOL ASETAT DARI RHIZOSFER ANGGREK TANAH Pecteilis susannae (L.) Rafin - Lasmini, Titi (LLDIKTI Wilayah X, 2015)
The objectives of this study were to isolate and identify yeast producing Indole-3-acetic acid from rhizosphere of terrestrial orchid Pecteilis susannae (L.) Rafin. This research commenced with the isolation of yeasts from rhizosphere of orchid P. susannae using Yeast Malt Agar (YMA) medium. Yeast isolates were selected based on growth experiment on Glucose Peptone Broth (GPB) supplemented with 200 Âµg/mL L-tryptophan. The IAA concentration was determined colorimetrically on spectrophotometer (OD530 nm) with Salkowskyâs reagent added to supernatant of yeast culture. Biomass (OD600 nm) and IAA production (OD530 nm) measured every 24 hours for 4 days. Identification of selected isolates carried out through macroscopic, microscopic, and biochemical properties. The results revealed that 29 isolates of yeast had been successfully isolated from rhizosphere of terrestrial orchid P. susannae (L.) Rafin, and only four isolates (K2, U5, A3 and A1) showed their capability to grow and produce high concentration of IAA on GPB. The fourth selected yeast isolates were identified as strain Saccharomyces sp.1 (K2), Saccharomyces sp.2 (U5), Cryptococcus sp.1 (A3), and Candida sp.1 (A1). Further evaluation of the selected rhizosphere yeast isolated producing IAA is necessary to be carried out to explore their potency as a source of hormone to promote plant growth.